A semi–dynamic, game based and interference aware channel assignment for multi–radio multi–channel wireless mesh networks. (12th December 2013) - Nezhad, Maryam Amiri; Cerdà–Alabern, Llorenç; Bellalta, Boris; Zapata, Manel Guerrero
Channel assignment (CA) has been extensively researched for multi–radio wireless mesh networks (WMNs), but it is still very challenging when it comes to its implementation. In this paper we propose a semi–dynamic and distributed CA mechanism called semi–dynamic interference aware channel assignment (SICA) based on game theory formulation. SICA is an interference aware, distributed CA which preserves the network connectivity without relying on a common channel nor central node for coordination between mesh routers. SICA applies a real time learner algorithm which assumes that nodes do not have perfect information about the network topology. To the best of our knowledge this is the first game formulation of CA which takes the co–channel interference into account. We have simulated SICA and compared against other channel assignment mechanisms proposed in the literature. Simulation results show that SICA outperforms other mechanisms.